Characterization of Methicillin-Resistant Staphylococcus aureus Isolated from Healthy Turkeys and Broilers Using DNA Microarrays - El-Adawy, Hosny; Ahmed, Marwa; Hotzel, Helmut; Monecke, Stefan; Schulz, Jochen; Hartung, Joerg; Ehricht, Ralf; Neubauer, Heinrich; Hafez, Hafez M. (Frontiers in Microbiology, 2016)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major human health problem and recently, domestic animals, in particular pigs and poultry are discussed as carriers and possible reservoirs of MRSA. Twenty seven S. aureus isolates from five turkey farms (n=18) and two broiler farms (n=9) were obtained by culturing of choana and skin swabs from apparently healthy birds, identified by Taqman-based real-time duplex nuc-mecA-PCR and characterized by spa typing as well as by a DNA microarray based assay which covered, amongst others, a considerable number of antibiotic resistance genes, species controls and virulence markers. The antimicrobial susceptibility profiles were tested by agar diffusion assays and genotypically confirmed by the microarray. Five different spa types (3 in turkeys and 2 in broilers) were detected. The majority of MRSA isolates (24/27) belonged to clonal complex 398-MRSA-V. The most frequently occurring spa types were accordingly t011, t034 and t899. A single CC5-MRSA-III isolated from turkey and CC398-MRSA with an unidentified/truncated SCCmec element in turkey and broiler were additionally detected. The phenotypic antimicrobial resistance profiles of S. aureus isolated from both turkeys and broilers against 14 different antimicrobials showed that all isolates were resistant to ampicillin, cefoxitin, oxacillin, doxycycline and tetracycline. Moreover, all S. aureus isolated from broilers were resistant to erythromycin and azithromycin. All isolates were susceptible to gentamicin, chloramphenicol, sulphonamides and fusidic acid. The resistance rate against ciprofloxacin was 55.6% in broiler isolates and 42.1% in turkey isolates. All tetracycline resistant isolates possessed genes tetK/M. All erythromycin-resistant broiler isolates carried ermA. Only one broiler isolate (11.1%) carried genes ermA, ermB and ermC, while 55.6% of turkey isolates possessed ermA and ermB genes. Neither PVL genes (lukF/S-PV), animal-associated leukocidin (lukM and luk-P83) nor the gene encoding the toxic shock syndrome toxin (tst1) were found in turkey and broiler isolates. In conclusion, the detection of MRSA in healthy turkeys and broilers with even additional antibiotic resistance markers is of major public health concern. The difference in antibiotic resistance and virulence markers between MRSA isolates from turkeys and broilers was addressed.